1992
DOI: 10.5547/issn0195-6574-ej-vol13-no4-11
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Disaggregated Price Elasticities in Industrial Energy Demand

Abstract: Econometric energy models are used to evaluate past policy experiences, assess the impact of future policies and forecast energy demand. This paper estimates an industrial energy demand model for the province of Ontario using a linear-logit specification for fuel type equations which are embedded in an aggregate energy demand equation. Short-term, long-term, own- and cross-price elasticities are estimated for electricity, natural gas, oil and coal. Own- and cross-price elasticities are disaggregated to show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…As shown in Table IV below, studies from the 80s and 90s roughly confkn the results about the short-run, but the long-run elasticity may be lo The fact that public ownership tends to have lower costs despite good reasons for why cost minimisation should not always be given the highest priority suggests that private firms are often inefficient, but it may also depend on public firms giving a strong and possibly excessive emphasis on commercial objectives. Benzen (1992) Denmark Chang and Hsing (1991) U.S. Dennerlein (1987) Germany (FRG) Donatos and Margos ( 1991) Greece Elkhafif ( 1992)d Canada Flaig (1990) Germany (FRG) Jackson (1 988)e U.S. Maddock ef ul. (1992) Colombia Magnus and Woodland (1987) The Netherlands Morss and Small (1989) U.S. Nan 8c Murry ( 1992)f U.S. Gstblom (1983) Sweden Pouris ( 1987) South Africa Rothman ( 1994) 53 countries Van Helden er al.…”
Section: Cost Differences and Demand Elasticity In The Light Of Ementioning
confidence: 99%
“…As shown in Table IV below, studies from the 80s and 90s roughly confkn the results about the short-run, but the long-run elasticity may be lo The fact that public ownership tends to have lower costs despite good reasons for why cost minimisation should not always be given the highest priority suggests that private firms are often inefficient, but it may also depend on public firms giving a strong and possibly excessive emphasis on commercial objectives. Benzen (1992) Denmark Chang and Hsing (1991) U.S. Dennerlein (1987) Germany (FRG) Donatos and Margos ( 1991) Greece Elkhafif ( 1992)d Canada Flaig (1990) Germany (FRG) Jackson (1 988)e U.S. Maddock ef ul. (1992) Colombia Magnus and Woodland (1987) The Netherlands Morss and Small (1989) U.S. Nan 8c Murry ( 1992)f U.S. Gstblom (1983) Sweden Pouris ( 1987) South Africa Rothman ( 1994) 53 countries Van Helden er al.…”
Section: Cost Differences and Demand Elasticity In The Light Of Ementioning
confidence: 99%
“…Elkhafif [43] showed that a substantial part of energy conservation come from the higher aggregate price of energy by estimating an industrial energy demand model for Ontario Province. In the case of China, Yuan, et al [44] proved that higher energy price would decrease energy consumption in China's industrial sectors.…”
Section: Granger Causality Testmentioning
confidence: 99%
“…Demand bidding can be considered as a subcategory from market-based programs category of demand response [5]. A wide range of literature has focused either on the measurement of load elasticity [6][7][8][9] or on the impacts of price responsiveness of loads on electricity prices in power markets [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%